Leierskapontwikkeling in 'n verplegingskollege - E. Harms; M. Muller (AOSIS, 1997)
This study is conducted within the context of nursing colleges and focuses on the empowerment of educational staff in a nursing college to facilitate excellence in leadership practice. A qualitative exploratory and descriptive study was conducted in different phases: the views and expectations of educational staff as leaders, as well as the views and expectations of the fourth year students as followers and potential professional leaders were explored and described by means of focus group interviews. A provisional conceptual framework for leadership development in a nursing college was compiled, exposed to a literature control and a final conceptual framework was refined, together with guidelines for leadership development in a nursing college. This article focuses on the final conceptual framework as well as the programme for leadership development in a nursing college. It is recommended that this programme be implemented and exposed to purposeful evaluation.